Why choose to become a teacher in China? A large-sample study using the Factors Influencing Teaching Choice scale. Issue 4 (8th August 2022) - Shang, Weiwei; Yu, Tianzuo; Wang, Ji; Sun, Di; Su, Jiming
ABSTRACT: China's education system faces a loss of teachers and a decline in education quality, and the new fertility policy means that the demand for teachers will increase. Against this background, the motivations and perceptions of pre-service teachers ( N = 2618) were investigated. The Factors Influencing Teaching Choice instrument was used, and its construct validity and reliability were assessed. The results indicate that social altruism motivation was the most influential, in contrast with the high ratings of perceived teaching ability and intrinsic value motivations in Western studies. Prior teaching and learning experience came next, highlighting the prominence of the practices of teacher education programmes. Female pre-service teachers reported significantly higher motivations from intrinsic career value and shaping the future of children/adolescents and fewer fallback-career motivations. With increasing college year, the study found significantly higher values for perception of high task demand. Social utility values and expert career were scored higher by rural pre-service teachers than by urban ones. It is argued that policy makers, politicians and others who care about improving students' intrinsic career value should enable pre-service teachers to undergo a longer internship time and targeted learning guidance.